Enzymatic Activity of Bromelain Isolated Pineapple (Ananas comosus) Hump and Its Antibacterial Effect on Enterococcus faecalis - Dewi Liliany; Armelia Sari Widyarman; Erni Erfan; Janti Sudiono; Melanie Sadono Djamil (Scientific Dental Journal, 2018)
Background: Enterococcus faecalis is the frequent cause of oral infections, such as periodontitis, infected root canals, and peri-radicular abscesses. Pineapple (Ananas comosus) fruit contains bromelain, one of proteolytic enzymes associated with several health benefits. Bromelain has been shown to promote healthy digestion, stimulate the immune system, improve cardiovascular conditions, and accelerate wound healing. Bromelain compounds possess anti-inflammatory and anticancer properties and exhibit antibacterial activity. Objective: To analyze the enzymatic activity of bromelain extracted from pineapple hump and investigate the antibacterial effect of bromelain against E. faecalis. Methods: Pineapple hump was dried and extracted with maceration technique. Further purification was obtained by ammonium sulfate fractionation, dialysis and ion exchange chromatography. Minimum inhibitory concentration (MIC) tests using diffusion and dilution techniques tested the antibacterial activity of the bromelain extract on E. faecalis. A one-way analysis of variance (ANOVA) test analyzed the significance of the differences in the E. faecalis inhibition zones after treatment with a range of bromelain extract concentrations. Differences were considered statistically significant if p < 0.05. Results: The specific activity of bromelain in the crude extract was 62.89 U/mg. Furthermore, bromelain activity using ammonium sulfate fractionation was 50.99 U/mg, dialysis was 54.59 U/mg, and ion exchange chromatography was 152.38 U/mg. The bromelain extract showed effective inhibitory and bactericidal activity against E. faecalis. The results of the inhibition test using a bromelain extract purified by ion exchange  chromatography demonstrated that a concentration as small as 12.5% was effective in inhibiting the growth of E. faecalis (p < 0.05). Conclusion: The highest enzymatic activity of bromelain was found after purification with ion exchange chromatography. Bromelain exerted an antibacterial effect against a potent endodontic pathogen, but further studies are needed to explore this effect.